LINGUISTIC ANALYSIS OF UZBEK LEGAL TERMS - Halimbekov Ibrohimjon Tursunovich; Khamdamova Muyassarkhon Nematovna (Modern American Journals, 2025)
The article examines the processes of improvement of Uzbek legal terms during the years of independence, the studies carried out in this regard, and their significance. It also examines the origin of legal terms, the degree of belonging to their own and assimilated layers, their structure, and structural analysis. The achievements and shortcomings in the process of nationalizing legal terms are reviewed. The tasks ahead, the responsibilities of lawyers and linguists, and research in this regard are clarified.